Efek Penambahan Bahan Aditif Non-Alami terhadap Perilaku Lempung Plastisitas Tinggi yang Distabilisasi dengan Semen - Soewignjo Agus Nugroho; Bambang Wisaksono; Heru Suharyadi (Eksergi, 2023)
Cement is proven increasing the strength of soft clays. Monmorillonite has a high shrinkage. Another hand, Kaolin has a small shrinkage. Waste material usage for stabilization agent was widely carried out this decade. BAFA (bottom ash fly ash) and POFA (palm oil fuel ash) are rich in Silica and Alumina, so they used to substitute of cement. The study examined the effect of Monmorillonite, Kaolin, BAFA and POFA on stabilization of clay with cement. Bentonite from 4% to 16% (is equated to BAFA and POFA, in ratio of 2:1) and Kaolin by 2.5%, used to reduce clay shrinkage, mixed with cement by 3% and 5%. Soil behavior will be reviewed from laboratory tests on curing-noncuring and soaked-unsoaked conditions. The results show changes in Atterberg Limits and Hydraulic Conductivity (permeability, k). Cement as well as BAFA and POFA reduce Plastic Limit greater than Liquid Limit. So, Plasticity Index decreased. It’s can be seen that cement and ash waste decreasing the permeability value. More Ash and less cement, make more impermeable soil. Addition of 3% and 5% cement increased the UCS values from 14.32 kPa to 81.20 kPa and 589.68 kPa and CBR value from 0.78% to 4.20% and 589.68 42.12% respectively